Predicting spinel solid solutions using a random atom substitution method. Issue 26 (28th June 2022) - Dickson, Robert C.; Manning, Troy D.; Raj, Edwin S.; Booth, Jonathan C. S.; Rosseinsky, Matthew J.; Dyer, Matthew S.
Abstract : The vc-ChemDASH methodology allows for the simultaneous evolution of composition and configuration of a system to find stable solid solutions. Abstract : Exploration of chemical composition and structural configuration space is the central problem in crystal structure prediction. Even in limiting structure space to a single structure type, many different compositions and configurations are possible. In this work, we attempt to address this problem using an extension to the existing ChemDASH code in which variable compositions can be explored. We show that ChemDASH is an efficient method for exploring a fixed-composition space of spinel structures and build upon this to include variable compositions in the Mn–Fe–Zn–O spinel phase field. This work presents the first basin-hopping crystal structure prediction method that can explore variable compositions.